PREJUDICE TOWARD PAPUAN STUDENTS: THE ROLE OF INTERGROUP ANXIETY, BELIEF, CONTACT QUANTITY, AND SOCIAL IDENTITY - Yenny Meliana; Marselius Sampe Tondok (Universitas Padjadjaran, 2023)
This study examined the relationship between social identity and prejudice against ethnic Papuan students with intergroup anxiety as mediators and quantity of contact and belief as moderators. This study using a quantitative cross-sectional survey design. Respondents (n=452) were students in Surabaya selected using accidental sampling. Data were collected online using Google Forms by employed several scales that were RIVEC (Rejection, Intimacy, Values, Emotions, and Culture) prejudice scale, a-three factors social identity scale, intergroup anxiety scale, contact quantity scale, and belief scale. The results of hypothesis testing showed that intergroup anxiety significantly mediates the relationship between social identity and prejudice against ethnic Papuan students (β= -0.25; p<0.001). The results also revealed the moderator roles of belief (β = -0.13; p<0.05) and quantity of contact (β = 0.07; p<0.05) in predicting prejudice. This finding can be concluded that the emotions associated with low intergroup anxiety play a role in mediated high social identity with low prejudice scores. Increased contact with outgroups did not guarantee a decrease in prejudice scores in people with high social identities. Still, the involvement of cognitive processes through positive beliefs by individuals acts as a buffer effect so that people with high social identities can decrease prejudice scores.